2014
DOI: 10.1002/chem.201303967
|View full text |Cite
|
Sign up to set email alerts
|

Towards the Fabrication of the Top‐Contact Electrode in Molecular Junctions by Photoreduction of a Metal Precursor

Abstract: Langmuir films of 4-{[4-({4-[(trimethylsilyl)ethynyl]phenyl}ethynyl)phenyl]ethynyl} benzenaminium chloride ([1 H]Cl) undergo anion metathesis when assembled on an aqueous auric acid (HAuCl4 ) subphase. Subsequent transfer to solid supports gives well-formed Langmuir-Blodgett (LB) monolayers of [1 H]AuCl4 in which the trimethylsilyl group serves as the surface contacting group. Photoreduction of the aurate on these monolayers leads to the formation of metallic gold nanoislands, which were distributed over the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 71 publications
0
18
0
Order By: Relevance
“…15,[26][27][28][29][30] A wide variety of techniques to deposit the top metal electrode onto a molecular monolayer have been described in the literature including direct and indirect evaporation, 11,[31][32][33][34][35][36][37][38] use of liquid metals, 11,34,39,40 flip chip lamination, 34,41 electrodeposition, [42][43][44] surface-diffusion-mediated deposition, 44 chemisorption of metal nanoparticles onto surface-functionalised monolayers, 45 thermal induced decomposition of an organometallic monolayer, 46 and photoreduction of a metal precursor. 47,48 The most significant problems in the deposition of the top-contact electrode are those related to damage of the functional molecules during the metallization process of the monolayer or penetration of the growing top-contact through the monolayer, which results in short circuits. In addition, many of the proposed 'soft' methods that avoid penetration of the growing metal electrode through the monolayer result in a relatively low surface coverage of the monolayer by the newly fashioned top contact.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,[26][27][28][29][30] A wide variety of techniques to deposit the top metal electrode onto a molecular monolayer have been described in the literature including direct and indirect evaporation, 11,[31][32][33][34][35][36][37][38] use of liquid metals, 11,34,39,40 flip chip lamination, 34,41 electrodeposition, [42][43][44] surface-diffusion-mediated deposition, 44 chemisorption of metal nanoparticles onto surface-functionalised monolayers, 45 thermal induced decomposition of an organometallic monolayer, 46 and photoreduction of a metal precursor. 47,48 The most significant problems in the deposition of the top-contact electrode are those related to damage of the functional molecules during the metallization process of the monolayer or penetration of the growing top-contact through the monolayer, which results in short circuits. In addition, many of the proposed 'soft' methods that avoid penetration of the growing metal electrode through the monolayer result in a relatively low surface coverage of the monolayer by the newly fashioned top contact.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, many of the proposed 'soft' methods that avoid penetration of the growing metal electrode through the monolayer result in a relatively low surface coverage of the monolayer by the newly fashioned top contact. [45][46][47] In this contribution, a simple procedure for the deposition of a metallic top-contact electrode onto a monolayer film of 'wire-like' molecules is presented. A self-assembled monolayer (SAM) of an oligo( phenylene ethynylene) (OPE) derivative, 4-(2-(4-(2-(4-aminophenyl)ethynyl)phenyl)ethynyl)benzenamine, 1, featuring amine functional groups to provide metallic contacts 49,50 has been used as the wire-like molecular component.…”
Section: Introductionmentioning
confidence: 99%
“…Charge transfer within ap eptidec an be defined electrochemically as attached to an electrode at one end and ar edox-active moiety at the other,o rm easured across two electrodes at am olecular junction.T he latter technique provides current/ voltage (I-V)c haracteristics of am olecule of interest bridged between the electrodes, through the application of an external potential. [2,7] Recent studies have shown that peptides can be used in the design of am olecular junction [8] using scanning probe techniques such as AFM, [9] and STM, [10] to measure the associated conductance. Significant work has also been reported on studying molecular junctionsb yt heoretical methods, using density functional theory (DFT) and Green's function techniques.…”
Section: Introductionmentioning
confidence: 99%
“…LB films of an organic compound incorporating a metal precursor, AuCl 4 -, from the subphase have been reported [271]. These LB monolayers were subsequently irradiated and photoreduction of the metal precursor results in gold nanoislands on top of the organic monolayer without destruction of the underlying organic film nor penetration of the nanoparticles.…”
Section: Deposition Of the Top Contact Electrodementioning
confidence: 98%